Tecendo meios de vida diversificados na agricultura familiar do tabaco - Ludtke, Fabiana Helma (2018)
The general objective of this work is to understand the constructions of processes of diversifications of livelihoods in family tobacco farming, through the examination of the resources used and the multiple relationships established by the families in the achievement of their diversifications activities. How are built (woven) strategies for diversifying livelihoods in family tobacco farming in the municipality of Candelária/RS? This questioning made necessary inquiries about: How the resources needed to achieve diversified activities are accessed and which relationships construct these forms of access? What diversification activities have been developed and what are the determinants of the capacity to diversify the livelihood in family tobacco farming? And the quality of participation of women in the process of achieving diversified livelihood? This analysis was based on the theoretical framework of the Livelihoods Approach, complemented by the Capabilities Approach. From the contributions of authors such as Ellis (2000), Bebbington (1999) and Sen (2008), it was possible to understand the activities developed by the families through the focus on the five capitals and the capabilities of access to them. This is a qualitative approach research, of the case study type. The sample of interest of this study were families that produce and that stopped to produce tobacco and that diversified their livelihoods in the rural environment of the municipality of Candelária RS. Twenty families of farmers were interviewed, representative of the research theme. It was observed that family farmers build their livelihoods diversified from activities (self-consumption or traditional) and resources (usually precarious) on properties. Along the trajectory they are strengthening and expanding their set of assets and activities, which represent important livelihoods to families to reduce dependence on tobacco cultivation. In this process, they expand their network of relationships and act more effectively in the main social domains (family, community, market and state). Through networks, families and individuals access different types of assets and actors needed to carry out, maintain and improve their activities, that is, to develop capabilities. The women participate actively in the processes of diversification acting in the construction of markets and with the actors of the State. They integrate production and marketing processes and, in some cases, act alone as protagonists in carrying out activities. Women's ability to achieve diversified livelihoods is mainly related to the expansion of their interpersonal networks. The key capabilities that need to be strengthened include: credit, land tenure and social security policies; ecological production processes; improvement of road infrastructure and communication; education and qualification; strengthening of organizational and community forms; democratization of spaces for demands; resumption and expansion of public purchases (PNAE and PAA); and strengthening of ATER services. It is concluded that these capabilities are fundamental to guarantee decent livelihoods for families.